1991
DOI: 10.1159/000247739
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Lupus erythematosus Exacerbated by Piroxicam

Abstract: A patient with Sjögren’s syndrome and seronegative polyarthritis is reported. After piroxicam intake and sun exposure she developed subacute cutaneous lupus erythematosus lesions with Ro antibodies. Despite drug withdrawal, typical cutaneous lesions and serological markers of systemic lupus erythematosus (SLE) progressively appeared. The use of piroxicam and other nonsteroidal anti-inflammatory drugs with photosensitizing potential in patients with Sjögren’s syndrome, sicca syndrome or a high suspicion of a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…SCLE skin lesions can occur in other clinical settings in which Ro ⁄SS-A autoantibody is seen, such as Sjögren syndrome and rheumatoid arthritis. 23 Our review revealed four patients with Sjögren syndrome who later developed DI-SCLE, [24][25][26] lending further support to the importance of the 8.1 ancestral haplotype immunogenetic background and Ro ⁄SS-A autoantibody production they both share. 27 The reverse is true as well.…”
Section: Are Histone Autoantibodies Significantly Associated With Drumentioning
confidence: 59%
See 1 more Smart Citation
“…SCLE skin lesions can occur in other clinical settings in which Ro ⁄SS-A autoantibody is seen, such as Sjögren syndrome and rheumatoid arthritis. 23 Our review revealed four patients with Sjögren syndrome who later developed DI-SCLE, [24][25][26] lending further support to the importance of the 8.1 ancestral haplotype immunogenetic background and Ro ⁄SS-A autoantibody production they both share. 27 The reverse is true as well.…”
Section: Are Histone Autoantibodies Significantly Associated With Drumentioning
confidence: 59%
“…The median incubation time was 6 weeks. The mean and median overall time 30 3 cases Nitrendipine 31 1 case Diuretics Hydrochorothiazide 3,10,22 10 cases Hydrochlorothiazide + triamterene 6 3 cases Chlorthiazide 5 2 cases Beta blockers Oxprenolol 32 4 cases Acebutolol 33 1 case Angiotensin-converting enzyme inhibitors Enalapril 10 2 cases Lisnopril 10 1 case Captopril 34 1 case Cilazapril 34 1 case Antifungals 30 of 117 reported cases: 25AE6% Terbinafine 12,14-16, [35][36][37] 29 cases Griseofulvin 13 1 case Chemotherapeutics 10 of 117 reported cases: 8AE5% Docetaxel 38 3 cases Paclitaxel 24, 38 3 cases Tamoxifen 39 2 cases Capecitabine 40, 41 2 cases Antihistamines 9 of 117 reported cases: 7AE7% Ranitidine 42 7 cases Brompheniramine 42 1 case Cinnarizine + thiethylperazine 43 1 case Immunomodulators 8 of 117 reported cases: 6AE8% Leflunomide 9,17,25, 44 5 cases Interferon a and b 10, 45 3 cases Antiepileptics 3 of 117 reported cases: 2AE6% Carbamazepine 46, 47 2 cases Phenytoin 48 1 case Statins 3 of 117 reported cases: 2AE6% Simvastatin 10, 49 2 cases Pravastatin 10 1 case Biologics 2 of 117 reported cases: 1AE7% Etanercept 50 1 case Efalizumab 51 1 case Proton pump inhibitors 2 of 117 reported cases: 1AE7% Lansoprazole 52 2 cases Nonsteroidal anti-inflammatory drugs 2 of 117 reported cases: 1AE7% Naproxen 53 1 case Piroxicam 26 1 case Hormone-altering drugs 2 of 117 reported cases: 1AE7% Leuprorelin 19 1 case Anastrozole 18 1 case Ultraviolet therapy 2 of 117 reported cases: 1AE7% PUVA 54 1 case PUVA and UVB 20 1 case Others 4 of 117 reported cases: 3AE4% Bupropion…”
Section: Resultsmentioning
confidence: 99%
“…These modulators may include immunosuppressive cytokines, such as IL-10 or VIP (25,26), but also lipid mediators of the PG family, such as PGE 2 , as demonstrated in the current study. Although PG were so far thought to mediate mainly proinflammatory effects, their involvement in IFN-a regulation may explain not only occasional reports about the induction of SLE-like symptoms by cyclooxygenase inhibitors (38), but also improvement of such symptoms by treatment with PGE 1 (39) and PGI analogs (40). Such beneficial effects have been mainly attributed to vasodilation and inhibition of thrombosis, whereas the effect of PG analogs on PDC-dependent IFN-a secretion and the costimulatory phenotype of PDC has so far not been considered.…”
Section: Discussionmentioning
confidence: 99%
“…1 Although all nonsteroidals have been associated with photosensitive rashes, only piroxicam has been reported to be associated with phototoxicity with resulting lupus ares. 18 Even though the overwhelming majority of SLE patients taking ibuprofen have no adverse reactions, case reports of aplastic anaemia, 19 ulcerative proctitis 20 and aseptic meningitis have appeared. [21][22][23][24] The latter represents one manifestation of a distinct hypersensitivity reaction characterized by hypotension, fever, rigors, conjunctivitis, nausea, arthralgias, elevated liver function tests and aseptic meningitis.…”
Section: Toxicity Of Nsaids In Slementioning
confidence: 99%